Generative AI for Young Children: New Pathways in Rehabilitation and Development: Kecerdasan Buatan Generatif untuk Anak Usia Dini: Jalur Baru dalam Rehabilitasi dan Perkembangan - Rati Sharma (Yayasan Nurul Musthafa, 2026)
Early childhood is a critical golden period for development; however, children experiencing neurodevelopmental delays often face late diagnosis and limited access to traditional face-to-face rehabilitation, particularly in low-resource settings like Nepal. This qualitative study employs a narrative interpretative approach to explore the potential of Generative Artificial Intelligence (AI) in supporting early childhood development and rehabilitation. Data were gathered through semi-structured interviews, classroom observations, and interactive workshops with a purposively sampled group of teachers, parents, and therapists. The thematic analysis reveals that Generative AI offers transformative opportunities across five core domains: acting as a patient digital conversational partner to boost speech and language skills ; transforming physical exercises into playful experiences using motion-based games and augmented reality (AR) ; facilitating adaptive cognitive growth through real-time adjusted problem-solving challenges ; coaching socio-emotional learning via safe virtual role-playing scenarios ; and breaking distance barriers through home-based tele-rehabilitation platforms. Nevertheless, stakeholders express vital ethical and practical concerns, including child data privacy risks, the dangerous impact of systemic inaccuracies, digital divides driven by limited hardware access, and the risk of reducing essential human touch. This study concludes that technology must never substitute human warmth, empathy, or love; instead, AI should complement human efforts under a